Biometric aspects of fruit and seed of Tamarindus indica L. - Sanches, Laura Araujo; Camargo, Alcilene Batista de; Garlet, Juliana (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
Tamarindus indica L. is a tree species very appreciated for ornamentation, being considered a multifunctional tree, since it can be used pulp, seeds, flowers, leaves, wood, bark, whether for nutritional or medicinal use. In addition, this species presents in its chemical composition amino acids, fatty acids, minerals, being outstanding for presenting excellent nutritional qualities. Thus, the present work aimed to characterize the biometry of fruits and seeds of Tamarindus indica L. For this, the biometry was performed using a random sample of 100 fruits and 100 seeds. Mass, length, width and thickness of fruits and seeds and number of seeds per fruit were evaluated. The fruits of Tamarindus indica presented average values of length, width, thickness and mass of: 59.72; 22.80; 15, 29 mm and 7.78 g respectively, with an average of three seeds per fruit. In the biometric analysis of the seeds we observed averages of length, width, thickness, and mass of 14.7; 10.15, 3.85mm and 1.12g respectively. The fruits and seeds of Tamarindus indica showed variability in their biometric characteristics, for the trees evaluated in this study. The fruits presented greater variation in length, while in the seeds it was observed greater variability in thickness and width.